Computer-Controlled Local Anaesthesia Delivery efficacy − a literature review - Katarzyna Janik; Wojciech Niemczyk; Robert Peterek; Rafał Rój; Agnieszka Balicz; Tadeusz Morawiec (Elsevier, 2024)
Minimising pain with effective local anaesthesia is an essential step towards improving the level of dentally anxious patients' comfort during dental treatment. It can be provided by many different techniques. One of them is using the Computer-Controlled Local Anaesthesia Delivery systems (CCLADs). This study was conducted to compare the efficacy of computerised anaesthesia with the conventional technique in terms of perceived pain. A database literature search was performed on PubMed, Cochrane Library and Google Scholar, covering up the period between 2015 and 2023. Only the studies comparing computerised anaesthesia technique with the use of conventional carpule were included. An overview of 20 relevant studies (n = 1347 subjects) was provided including pediatric patients, as well as the adults. The evaluated parameters were: pain, child's behaviour, heart rate, blood pressure, level of satisfaction, anxiety, further anaesthesia method preference, need for additional anaesthetic, as well as the duration of anaesthesia, measured by different scales, devices and questionnaires. The present literature review led the authors to the conclusion, that the use of CCLADs is significantly less painful than the traditional anaesthesia and it is a promising technique for helping patients deal with pain perception. However, it is advisable to conduct further research on the use of CCLAD.